El indigenismo de Maximiliano en México, 1864-1867 - Jancsó Katalin (Acta hispanica, 2009)
The aim of our study is to examine an interesting period of Mexican history: the empire of Maximilian I, born Archduke Ferdinand Maximilian Joseph of Austria. After a short introduction to the Hungarian historiography of the topic, the 19th century turbulent history of Mexico, the circumstances of the French intervention and the emperor’s ascendance to the throne, we concentrate on the analysis of Maximilian’s attitude towards indigenous people. Influenced by French socialists, Maria Theresa’s illustrated absolutism and contemporary liberalism, the emperor tried to alleviate the painful effects of liberal reforms introduced in 1856. He himself introduced several reforms, especially in land property questions and community rights. He created a protection committee for miserable classes, whose work helped him take several measurements in favour of Mexican indigenous people. Nevertheless, the empire was doomed to fail. Maximilian and his generals were executed in June, 1867, which also meant the end of an important period of battles between liberals and conservatives.